Contractile fibroblasts form a transient niche for the branching mammary epithelium - Sumbal, Jakub; Journot, Robin P.; Attri, Kriti; Danek, Veronika; Merle, Candice; Faraldo, Marisa M.; Sumbalova Koledova, Zuzana; Fre, Silvia (Nature communications, 2025)
Fibroblasts are stromal cells found in connective tissue that are critical for organ development, tissue homeostasis and pathology. Single-cell transcriptomic analyses have revealed a high level of inter- and intra-organ heterogeneity of fibroblasts. However, the functional implications and lineage relations of different fibroblast subtypes remained unexplored, especially in the mammary gland. Here, we provide a comprehensive characterization of pubertal mouse mammary fibroblasts, through single-cell RNA sequencing, spatial mapping, functional assays, and in vivo lineage tracing. We unravel a transient niche-forming population of specialized contractile fibroblasts that exclusively localize around the tips of the growing mammary epithelium and are recruited from preadipocytes in the surrounding fat pad stroma. Using organoid-fibroblast co-cultures we reveal that different fibroblast populations can acquire contractile features when in direct contact with the epithelium, promoting organoid branching. The detailed in vivo characterization of these specialized cells and their lineage history provides insights into fibroblast heterogeneity and implicates their importance for creating a signalling niche during mouse mammary gland development. Fibroblasts represent a heterogenous cell population but how their differences reflect their plasticity and origin is not fully understood. Here, the authors map the origin and fate of a transient contractile fibroblast population that forms a niche supporting pubertal mammary gland branching and growth.